2020
DOI: 10.13057/biodiv/d210935
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and compound constituents of gamma-irradiated black rice (Oryza sativa L.) var. Cempo Ireng indigenous of Indonesia

Abstract: Abstract. Suryanti V, Riyatun, Suharyana, Sutarno, Saputra OA. 2020. Antioxidant activity and compound constituents of gamma-irradiated black rice (Oryza sativa L.) var. Cempo Ireng Indigenous of Indonesia. Biodiversitas 21: 4205-4212. Nowadays, black rice is gaining consumer interest because of its health benefit. Due to the high content of antioxidant compounds such as phenolics and flavonoids, the nutritional profile of black rice is much better than any other rice varieties. Anthocyanins, pigment with powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Results showed that mutant Cempo Ireng plant was superior compared to the control. The treatment with gamma-ray at 200 Gy showed significantly decrease the flowering age and plant heigh, and also increase the grain yield, grain weight, protein content, and anthocyanin concentration (Table 3) [6,17,29,37,38,39,40,41,42,43,44]. Mutations not only affect the morphological traits of Cempo Ireng, including plant height, grain weight, flowering age, number of grains per panicle, panicle type, apiculus color, grain color, leaf-blade color, ligule color, auricle color, leaf angle, and leaf surface but also affect the nutrition contents such as anthocyanin, protein, and amylase; and enhance the stress tolerance.…”
Section: Mutation Lines Of Cempo Irengmentioning
confidence: 99%
“…Results showed that mutant Cempo Ireng plant was superior compared to the control. The treatment with gamma-ray at 200 Gy showed significantly decrease the flowering age and plant heigh, and also increase the grain yield, grain weight, protein content, and anthocyanin concentration (Table 3) [6,17,29,37,38,39,40,41,42,43,44]. Mutations not only affect the morphological traits of Cempo Ireng, including plant height, grain weight, flowering age, number of grains per panicle, panicle type, apiculus color, grain color, leaf-blade color, ligule color, auricle color, leaf angle, and leaf surface but also affect the nutrition contents such as anthocyanin, protein, and amylase; and enhance the stress tolerance.…”
Section: Mutation Lines Of Cempo Irengmentioning
confidence: 99%
“…Results showed that mutant Cempo Ireng plant was superior compared to the control. The treatment with gammaray at 200 Gy showed signifi cantly decrease the fl owering age and plant heigh, and also increase the grain yield, grain weight, protein content, and anthocyanin concentration (Table 3) [6,17,29,[37][38][39][40][41][42][43][44]. Mutations not only aff ect the morphological traits of Cempo Ireng, including plant height, grain weight, fl owering age, number of grains per panicle, panicle type, apiculus color, grain color, leaf-blade color, ligule color, auricle color, leaf angle, and leaf surface but also aff ect the nutrition contents such as anthocyanin, protein, and amylase; and enhance the stress tolerance.…”
Section: Mutation Lines Of Cempo Irengmentioning
confidence: 99%
“…Effect of gamma-ray irradiation in Cempo Ireng[6,17,29,[37][38][39][40][41][42][43][44].Means followed with the same letter in the same column had no signifi cant difference on mood median test level of 5%.…”
mentioning
confidence: 99%
“…Black rice is a type of pigmented rice that is known as a functional food. Its health benefits can prevent cardiovascular disease, reduce the risk of diabetes and obesity, and prevent the spread of cancer cells [1][2][3][4]. This advantage is related to the high nutritional content, antioxidant activity, and low glycaemic index.…”
Section: Introductionmentioning
confidence: 99%